Development of Digital Teaching Materials for Indonesian Phonetics with Sound Association Design for Basic Level BIPA Arabic Learners - Yoviyani, Salis Hilda; Mulyati, Yeti; Sastromiharjo, Andoyo; Halimah, Halimah (LPPM Universitas Pendidikan Mandalika, 2024)
This research aims to develop digital teaching materials for Indonesian phonetics designed with sound association to support basic-level BIPA learners. This research method used research and development with the 4-D model, which consists of Define, Design, Develop, and Disseminate stages. The research instruments included pronunciation ability tests, learner needs questionnaires, BIPA teacher interview instruments, and validation sheets from experts and practitioners. The data analysis techniques used were qualitative and quantitative methods and Gregory's validity test with validity assessment criteria using the Likert Scale 1-4. The validation results indicated that the materials were